PERAN REGULASI TEKNOLOGI DAN KARYAWAN BANK UNTUK MENCEGAH TINDAK PENCUCIAN UANG DI BANK - Pratama, Wilson Candra Teguh; Fatkhurrokhman, Tiyan; Anggoro, Wisanggeni Bagus; Ramlah, Sri; Barokah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
Banks, commonly utilized as financial institutions, are often implicated in money laundering activities. The majority of these institutions report suspicious transactions to the Indonesian Financial Transaction Reports and Analysis Center (PPATK). This study seeks to assess the influence of implementing regulatory technology (regtech) and the involvement of Anti Money Laundering (AML) officers in preventing money laundering within a bank. Employing explanatory research to test hypotheses, the primary data collection involved a questionnaire distributed to 689 AML officers in Indonesia, with a 42.9% response rate from 296 participants. Multivariate analysis results indicate that electronic know-your-customer (KYC) lacks significance in preventing money laundering. Conversely, transaction monitoring, along with considerations of cost and time, demonstrates a positive and significant impact on thwarting money laundering. Additionally, there is a notable positive effect between bankers' competency and awareness in preventing money laundering. Both Regulatory Technology and bankers play crucial roles in averting money laundering. Notably, research concerning technology and bankers in the context of money laundering prevention remains limited in Indonesia. This study contributes valuable insights to existing literature on anti-money laundering and the progression of anti-money laundering systems.